How do expectations about the macroeconomy affect personal expectations and behavior? - Christopher Roth; Johannes Wohlfart (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2018)
Using a representative online panel from the US, we examine how individuals' macroeconomic expectations causally affect their personal economic prospects and their behavior. To exogenously vary respondents' expectations, we provide them with different professional forecasts about the likelihood of a recession. Respondents update their aggregate economic outlook in response to the forecasts, extrapolate to expectations about their personal economic circumstances and adjust their consumption behavior and stock purchases. Extrapolation to expectations about personal unemployment is driven by individuals with higher exposure to macroeconomic risk, consistent with sticky information models in which people are inattentive, but understand how the economy works.
urn:nbn:de:hebis:30:3-488037
Keywords: D12; D14; D83; D84; E32; G11; 330; Expectation Formation; Information; Updating; Aggregate Uncertainty; Macroeconomic Conditions